Cut Off from New Competition: Threat of Entry and Quality of Primary Care - Eduard Brüll; Davud Rostam-Afschar; Oliver Schlenker (Global Labor Organization (GLO), 2024)
We study how the threat of entry affects service quantity and quality of general practitioners (GPs). We leverage Germany's needs-based primary care planning system, in which the likelihood of new GPs reduces by 20 percentage points when primary care coverage exceeds a cut-off. We compile novel data covering all German primary care regions and up to 30,000 GP-level observations from 2014 to 2019. Reduced threat of entry lowers patient satisfaction for incumbent GPs without nearby competitors but not in areas with competitors. We find no effects on working hours or quality measures at the regional level including hospitalizations and mortality.
Keywords: I11; I18; J44; J22; L10; L22; R23; 330; Entry regulation; general practitioners; healthcare provision; threat of entry; regression discontinuity design